1989
DOI: 10.1177/0310057x8901700327
|View full text |Cite
|
Sign up to set email alerts
|

A Fatal Case of Pulmonary Oedema in a Healthy Young Male following Naloxone Administration

Abstract: with spina bifida cystica and severe kyphosis. Full cooperation between obstetric and anaesthetic teams, a thorough examination of the patient and a detailed explanation of spinal anaesthesia are considered essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0
1

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…Pulmonary oedema has been reported but most instances have occurred in the postoperative period [33][34][35][36][37][38][39] or in the presence of pre-existing cardiorespiratory disease, 40 and in many of these reports it can be difficult to differentiate between the effect of naloxone and the effect of the underlying disease process or other drugs that have been ingested or administered. Many episodes of pulmonary oedema secondary to opioid toxicity have been published since it was first noted by William Osler in the 1880s 5 41-50 and it has been suggested that naloxone simply reveals the opioid induced pulmonary oedema that had been masked by the respiratory depression.…”
mentioning
confidence: 99%
“…Pulmonary oedema has been reported but most instances have occurred in the postoperative period [33][34][35][36][37][38][39] or in the presence of pre-existing cardiorespiratory disease, 40 and in many of these reports it can be difficult to differentiate between the effect of naloxone and the effect of the underlying disease process or other drugs that have been ingested or administered. Many episodes of pulmonary oedema secondary to opioid toxicity have been published since it was first noted by William Osler in the 1880s 5 41-50 and it has been suggested that naloxone simply reveals the opioid induced pulmonary oedema that had been masked by the respiratory depression.…”
mentioning
confidence: 99%
“…Nausea and vomiting have occurred, with seizures reported infrequently. Individual reports of hypertension, pulmonary oedema, and cardiac arrhythmias have generally been in patients with pre-existing heart disease undergoing cardiac surgery,10 and the role of naloxone in two reported cases of pulmonary oedema in healthy young men11 12 has since been questioned 13. The National Poisons Information Service in London reported that it had never been informed of a suspected adverse reaction to naloxone despite being contacted by about 800 cases of opioid poisoning each year 14…”
Section: Home Based Supplies Of Naloxone Would Save Livesmentioning
confidence: 99%
“…Typischerweise ist der Patient dabei intoxikationsbedingt komatös, bradypnoeisch und zyanotisch; über der Lunge können Rasselgeräusche auskultiert werden. Interessanterweise gibt es auch Berichte über das Auftreten von Lungenödem nach der Gabe von Naloxon bei der Behandlung von Opiatvergiftungen[5,20,43] und sogar nach Gabe von Naloxon ohne vorherige Opiatvergiftung[37]. Das Röntgenbild der Lunge zeigt das typische Bild eines Lungenödems, wobei die Herzkontur schmal ist.…”
unclassified